Preparation of chlorine-doped Cu2O octahedral material and application of chlorine-doped Cu2O octahedral material in CO2 photocatalytic alcohol preparation

By doping chloride ions on the surface of Cu2O material to form chlorine-doped octahedral Cu2O material, the problems of low efficiency and poor stability in the CO2 conversion process are solved, and the effect of efficient photocatalytic CO2 alcohol production is achieved.

CN119819330APending Publication Date: 2025-04-15NORTHWEST UNIVERSITY FOR NATIONALITIES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510081620.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

In the photocatalytic CO2 conversion process, traditional semiconductor photocatalytic materials have problems such as low conversion efficiency and low selection rate of liquid alcohol products and polycarbon products. Cu2O materials are prone to photocorrosion during light illumination and have weak stability.

Method used

Octahedral Cu2O particles were prepared by glucose reduction method, and chloride ions were doped on their surfaces by hydrothermal method to form chlorine-doped octahedral Cu2O materials, improving their band gap structure and light stability.

Benefits of technology

The efficiency and product selectivity of the photocatalytic reaction are improved, the photostability of Cu2O materials is enhanced, and the yield of methanol and ethanol is significantly improved, with a selection rate of 94%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119819330A_ABST
    Figure CN119819330A_ABST
Patent Text Reader

Abstract

The invention discloses preparation of a chlorine-doped Cu2O octahedral material and application of the chlorine-doped Cu2O octahedral material in CO2 photocatalytic alcohol preparation. Rhombic octahedral Cu2O particles are prepared through a glucose reduction method, then O vacancy-rich rhombic octahedral Cu2O with Cl-doped surfaces is prepared through a hydrothermal method, and Cl-is doped in the octahedral Cu2O, so that the band gap structure of Cu2O is improved, the density of the O vacancies on the surfaces of Cu2O is improved, compounding of electrons and holes is improved, and the photoelectric conversion efficiency is improved. The transfer of photon-generated carriers is accelerated and the adsorption of CO2 on the surface of the photon-generated carriers is enhanced, so that the efficiency of photocatalytic reaction is improved. In the photoreaction process, water molecules and CO2 molecules in a reactor are adsorbed on the surface of the composite catalyst, so that water, the photocatalyst and CO2 are in better contact, the performance of photocatalytic reduction of CO2 is improved, and the composite catalyst is used in the reaction of photocatalytic reduction of CO2 and has high yield of methanol and ethanol.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of photocatalytic technology and relates to a method for photocatalytic CO 2 Photocatalyst for alcohol production and preparation method thereof, particularly a method for photocatalytic CO 2 Chlorine-doped Cu for alcohol production 2 O octahedral material and preparation method thereof. Background Art

[0002] Environmental problems and energy shortages are two major challenges facing social development in the 21st century. In 2023, the global CO 2 Annual emissions reached 37.4 billion tons, CO 2 Excessive emissions of CO2 will cause global warming, sea level rise, ecological pollution and other environmental problems. On the other hand, energy shortage is one of the main problems hindering social and economic development, and the excessive use of traditional energy such as coal and oil will cause CO2 to 2 The emission of CO2 will further increase, thus falling into a contradictory cycle between energy and environment. 2 Green conversion into available clean energy is an important strategy to solve environmental problems and energy shortages. In recent years, scholars have studied and synthesized various catalytic materials and achieved CO conversion through electrocatalysis, photocatalysis, thermal catalysis, photothermal catalysis and photoelectrocatalysis. 2 To CO, CH 4 , C 2 H 6 , CH 3 OH and other products. Among them, photocatalysis is the greenest conversion pathway, which uses infinite sunlight as the main energy source, realizes redox reaction with the help of photocatalytic materials, and does not produce secondary pollution to the environment during the reaction process. It is currently the solution to CO 2 Photocatalysis is the most ideal strategy for catalytic conversion. Unlike electrocatalysis and thermal catalysis, photocatalysis has higher thermal energy to participate in the reaction. 2 The conversion has problems such as low conversion efficiency, low selectivity of liquid phase alcohol products and multi-carbon products, which also hinder the photocatalytic CO 2 Further development of restoration.

[0003] Photocatalytic materials, as the core of photocatalytic reactions, directly determine the efficiency of photocatalytic reactions and the selectivity of products. However, traditional semiconductor photocatalytic materials have defects such as narrow photoreaction range, poor bandgap structure, poor electron-hole separation efficiency, and short photogenerated carrier lifetime. Therefore, a large number of scholars are determined to improve the activity of photocatalytic reactions through modification and compounding of traditional semiconductor catalytic materials. 2 In the reduction research, Cu-based materials not only have rich element reserves, but also have low cost and are easy to use. 2The molecule has a strong adsorption effect and is a natural CO 2 Reduction catalytic materials. In Cu-based semiconductor materials, Cu 2 O not only has a suitable valence band and conduction band position, but also has a band gap width of about 2.2eV, which gives it a large light response range and can effectively utilize visible light, which accounts for 42-43% of sunlight. Liu et al. used a correlation scanning fluorescence X-ray microscope and an environmental transmission electron microscope at normal pressure and combined them with DFT calculations to confirm the atomic level of Cu 2 The (110) crystal plane of O is CO 2 The reduction to methanol has extremely high photocatalytic activity and selectivity. 2 Photocatalytic reduction of CO by O cubic crystals 2 The internal quantum yield of methanol production is ~72%. 2 O has CO 2 High selective reduction to alcohol products. 2 O is mostly used for electrochemical catalysis of CO 2 The research on reduction of CuO is very limited in its application in photocatalysis, mainly because it is prone to photocorrosion during illumination and has weak photostability. The main reason for photocorrosion is that when Cu 2 After irradiation, O + The stability is weak, and most of the electrons and holes generated by it participate in its own disproportionation reaction to generate Cu 0 and CuO. So how to improve the separation efficiency of electrons and holes while making the photogenerated carriers transfer quickly and participate in CO 2 Reduction and H 2 The oxidation process of O is to improve the photocatalytic activity and Cu 2 O is the key to photostability. 2 In the process of modifying O materials, it was found that appropriate ion doping in semiconductors is conducive to the generation of a large number of defects on the semiconductor surface, and these defects can bind the generated electrons and accelerate the transfer of electrons. At the same time, it also adjusts the band gap structure of the semiconductor material, broadens the light response range of the material, achieves the improvement of photocatalytic efficiency and the specific selection of products and improves Cu 2 O stability. In addition, experiments have shown that the main active sites of ion-doped semiconductor materials are the surface-doped ions and the generated vacancies. When ions are doped inside the semiconductor, they have almost no promoting effect on the photocatalytic activity. Therefore, how to dope more ions on the semiconductor surface to provide more active sites during the reaction is the key to improving the catalytic activity of ion-doped photocatalytic materials. Summary of the invention

[0004] The present invention aims to disclose a chlorine-doped Cu2 Preparation method of O octahedral material and its use as photocatalyst for catalytic reduction of CO 2 Application in alcohol production.

[0005] 1. Chlorine-doped Cu 2 Preparation of O octahedral materials 1) Dissolve copper acetate in deionized water, then add NaOH and glucose, heat in a 60-80℃ water bath and stir continuously until the solution color no longer changes, cool to room temperature, centrifuge to obtain the precipitate, wash, and vacuum dry to obtain octahedral Cu 2 O particles, denoted as OCu 2 O; The molar ratio of copper acetate to glucose is 4:1-6:1, and the molar ratio of NaOH to glucose is 25:1-35:1.

[0006] 2) Place OCu 2 O was dispersed in deionized water by stirring, and then NH 4 Cl, react at 120~140℃ for 4~8h. After the reaction is completed, cool to room temperature, centrifuge to obtain the precipitate, wash, and vacuum dry to obtain chlorine-doped octahedral Cu 2 O particles, denoted as Cl-OCu 2 O; The OCu 2 O and NH 4 The mass ratio of Cl is 8:1~20:1.

[0007] The present invention first prepares rhombic octahedral Cu by glucose reduction method. 2 O particles, and then surface Cl-doped O-vacancy-rich rhombic octahedral Cu was prepared by hydrothermal method. 2 O, through Cl - In octahedral Cu 2 O doping improves the Cu 2 O band gap structure and increase the density of O vacancies on its surface, thereby improving the recombination of electrons and holes, accelerating the transfer of photogenerated carriers and enhancing the surface CO 2 adsorption.

[0008] 2. Octahedral Cu 2 O materials and chlorine-doped Cu 2 Structural characterization of O materials 1. TEM and SEM testing Figure 2 The prepared rhombic octahedral Cu 2 O and Cl doped Cu 2 SEM and TEM images of O. Figure 2 It can be seen from (a) and (b) that Cu2 O and Cl doped Cu 2 O is uniformly dispersed particles without a large amount of aggregation. Different from the previous ion doping, due to the ion doping in the process of crystal formation, 2 O will inhibit Cu 2 O grows on the (110) crystal plane, thus changing the Cu 2 The morphology of O crystals. From the SEM, it can be seen that Cl is doped into the formed Cu by hydrothermal 2 The surface of O octahedron did not change after Cu 2 O crystal surface growth, and for OCu 2 The crystal structure of O is almost unaffected, so that the highly active crystal faces of the material are preserved. Figure 2 (d), (e) are OCu 2 O and Cl-OCu 2 O TEM, it can be seen that the synthesized Cu 2 O can be slightly truncated, which also increases the CO 2 2 (f) is the contact area of ​​the prepared Cl-Cu 2 HRTEM image of O-20. It can be seen from the figure that in Cu 2 Two obvious lattice fringes can be observed on the surface of the O crystal. The widths of the lattice fringes are about 0.25nm and 0.22nm, corresponding to Cu 2 O's (111) and (220) crystal planes.

[0009] 2. X-ray photoelectron spectroscopy test Figure 3 (a) is the full XPS spectrum of the prepared sample. Due to the small amount of Cl doped on the surface, it is difficult to see the obvious Cl binding energy peak in the full spectrum. Figure 3 (d) It can be seen that the binding energies of the two main peaks of Cu 2p3 / 2 and Cu 2p1 / 2 are 932.20 eV and 952.13 eV, respectively, corresponding to Cu 2 Lattice Cu+ in O, 934.11eV and 954.10eV are Cu 2+ The binding energy of Cl-doped Cu 2 O also showed obvious satellite peaks, which may be due to long-term exposure to air. 2 A small part of the O crystal surface is oxidized to CuO. This also shows that Cl doping makes Cu 2 O's stability is enhanced and it is less susceptible to the effects of light and oxygen in the air. Figure 3 (c) It can be seen that OCu 2The three binding energy peaks of O1s of O are located at 529.83eV, 531.66eV, and 532.42eV, corresponding to lattice O, OV (oxygen vacancy), and adsorbed O, respectively. 2 The position of the lattice O of O529.86 was slightly shifted after Cl doping, and the ratio of the area of ​​the OV binding energy peak to the area of ​​the O lattice binding energy peak increased significantly, indicating that Cl doping further caused the formation of surface O vacancies, which is beneficial for the separation of electrons and holes and the rapid transfer of photogenerated carriers. Figure 3 As can be seen in (b), the two binding energy peaks of Cl 2p appear at 198.58 eV and 200.16 eV, respectively, which can be attributed to the energy peaks of Cl 2p3 / 2 and Cl 2p1 / 2, thus proving that chlorine can be incorporated into Cl-doped Cu 2 O exists in the form of Cu-Cl bonds in the lattice.

[0010] 3. Electrochemical test Figure 4 (a) Transient photocurrent test and (b) electrochemical impedance spectroscopy. Figure 4 (a) The photocurrent response analysis shows that there is a clear photocurrent signal in all samples and the response intensity is highly reproducible during switching. 2 Compared with O 2 The difference between the photocurrent and dark current of O and Cl-OCu 2 O is about 2.5 times higher than that of the O. This indicates that the construction of oxygen vacancies and the doping of Cl ions effectively improve the separation efficiency of photogenerated carriers. Figure 4 (b) Electrochemical impedance spectroscopy (EIS) provides further evidence of charge transfer resistance. 2 O samples have higher transient photocurrent intensity and smaller semicircle radius, which means they have higher charge separation and transfer efficiency. This shows that the construction of oxygen vacancies and the doping of Cl ions effectively improve the separation and transfer efficiency of photogenerated carriers, which is an important reason for the improvement of photocatalytic activity.

[0011] 3. Octahedral Cu 2 O materials and chlorine-doped Cu 2 Photochemical performance test of O materials Photocatalytic reduction of CO 2 The experiment includes two parts: photoreduction and reduction product detection. The experimental setup includes a 50 mL quartz glass reactor with a top window, a 300 W xenon lamp located 8 cm above the reactor, and an offline gas chromatograph (GC9790Ⅱ gas chromatograph), which is equipped with a flame ionization detector (FID), a thermal conductivity detector (TCD), and a N2 As carrier gas; UV lamp (300nm<λ<2500nm, 20.5mW·cm -2 ) light emitter. During the experiment, add 50 mL of deionized water to the bottom of the reactor, and then spread 0.5 g of sample catalyst powder on the bottom of the reactor. To ensure that the experiment is not disturbed, CO should be continuously introduced into the reactor. 2 (99.0%) for half an hour, with the reactor temperature maintained at approximately 25°C by cooling it with circulating water. First, a blank run was performed to ensure that any carbon-based products measured by GC were derived from CO2. Second, a test was performed in an empty reactor with CO2 and water as reactants, and no hydrocarbons were detected in the dark or under illumination, indicating that CO2 reduction did not occur in the absence of a catalyst.

[0012] Figure 5 Octahedral Cu 2 O materials and chlorine-doped Cu 2 O material photochemical performance test diagram. The results show that compared with the original OCu 2 Compared with O, Cl-doped OCu 2 O significantly enhanced the formation of methanol and ethanol, which may be due to the reduction of electron-hole recombination. 2 The methanol yield of O octahedron is 643.89 μmol·g -1 , ethanol yield was 85.45 μmol·g -1 , Cl-OCu 2 The methanol yield of O-10 was 1440.80 μmol·g -1 , ethanol yield was 110.48 μmol·g -1 , Cl-OCu 2 The methanol yield of O-15 was 1469.51 μmol·g -1 , ethanol yield was 124.32 μmol·g -1 , Cl-OCu 2 The methanol yield of O-25 was 1451.26 μmol·g -1 , ethanol yield was 115.87 μmol·g -1 When NH 4 When the Cl doping amount reaches 20 mg, the Cl-OCu 2 O-20 has the highest reduction efficiency, with a methanol yield of 2365.73 μmol·g in 5 h. -1 The yield of ethanol was 150.06 μmol·g -1 , where methanol is the main product with a selectivity of 94%; when NH 4When the doping amount of CL is less than 20 mg, its photocatalytic performance gradually improves with the increase of doping amount, which may be due to the gradual increase of the density of oxygen vacancies on its surface. 4 When the doping amount of CL reaches 25 mg, Cl-OCu 2 O-25 compared to Cl-OCu 2 The catalytic efficiency of O-20 was significantly reduced, which may be because the excessive Cl doping filled the O vacancies generated on the surface that were conducive to the reduction reaction and made the CO 2 Cu adsorption activation site + covered, resulting in decreased activity.

[0013] The present invention has the following beneficial effects: The present invention uses glucose reduction method to prepare octahedral Cu 2 O crystals, and then successfully prepared Cl-doped octahedral Cu by hydrothermal method. 2 O semiconductor. The introduction of Cl adjusts the band structure of the material and enhances the absorption intensity in the ultraviolet-visible range of 300-600nm. The rich O vacancies on the crystal surface caused by Cl doping make the photocatalytic reaction on the catalyst surface better, thereby improving the efficiency of the photocatalytic reaction. During the photoreaction process, water molecules and CO in the reactor 2 The molecules are adsorbed on the surface of the composite catalyst, making water, photocatalyst and CO 2 Better contact improves photocatalytic reduction of CO 2 Performance for photocatalytic reduction of CO 2 The reaction has a higher yield of methanol and ethanol. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 The octahedral Cu prepared by the present invention 2 O materials and chlorine-doped Cu 2 O material preparation flow chart.

[0015] Figure 2 The octahedral Cu prepared by the present invention 2 O materials and chlorine-doped Cu 2 SEM and TEM images of O materials, including: (a) OCu 2 SEM of O, (b) Cl-OCu 2 SEM of O-20, (c) Cl-OCu 2 Element distribution map of O-20; (d) OCu 2 TEM of O, (e)Cl-OCu 2 TEM of O-20.

[0016] Figure 3 The octahedral Cu prepared by the present invention2 O materials and chlorine-doped Cu 2 X-ray energy spectrum of O material.

[0017] Figure 4 The octahedral Cu prepared by the present invention 2 O materials and chlorine-doped Cu 2 (a) Transient photocurrent test and (b) electrochemical impedance spectroscopy of O materials.

[0018] Figure 5 Octahedral Cu 2 O materials and chlorine-doped Cu 2 Photochemical performance test diagram of O material, where: (a) is methanol yield, (b) is ethanol yield. DETAILED DESCRIPTION

[0019] The present invention is further explained below with reference to specific embodiments.

[0020] Example 1 Octahedral Cu 2 O was prepared by glucose reduction, 0.015 mol copper(II) acetate (Cu(OAc) 2 ) was dissolved in 40 mL of deionized water and placed at 70 ◦ C water bath, stirring continuously at 700 rpm for 5 min. Add 10 mL 9.0 M NaOH solution to the copper acetate aqueous solution and quickly add 0.6 g glucose within 4 seconds. The solution continued to stir at 70 ° C for about 60 minutes, then stopped stirring and cooled to room temperature. The collected precipitate was repeatedly washed three times with anhydrous ethanol and deionized water. Finally, the powder was dried in a vacuum oven at 60 ° C for 6 hours to obtain Cu 2 O particles, denoted as OCu 2 O.

[0021] Photochemical performance test: OCu 2 O for photocatalytic reduction of CO 2 , methanol yield was 643.89 μmol·g -1 , ethanol yield was 85.45 μmol·g -1 .

[0022] Example 2 Weigh 0.2g OCu 2 O was dispersed in 40 ml of deionized water, and then 0.02 g of NH 4Cl, the solution was stirred for 20 minutes and then ultrasonically treated for 40 minutes. The solution was placed in a 50 ml stainless steel reactor lined with polytetrafluoroethylene and reacted at 120°C for 6 hours. After the solution was cooled to room temperature, the collected precipitate was repeatedly washed three times with anhydrous ethanol and deionized water. After drying in a vacuum oven at 60°C for 6 hours, the Cl-doped octahedral Cu 2 O particle samples, prepared Cl-doped Cu 2 O octahedral particle samples were recorded as Cl-OCu 2 O-20.

[0023] Photochemical performance test: Cl-OCu 2 O-20 for photocatalytic reduction of CO 2 The yield of methanol was 2365.73 μmol·g -1 The yield of ethanol was 150.06 μmol·g -1 .

[0024] Example 3 Weigh 0.2g OCu 2 O was dispersed in 40 ml of deionized water, and then 0.01 g of NH 4 Cl, the solution was stirred for 20 minutes and then ultrasonicated for 40 minutes. The solution was placed in a 50 ml stainless steel reactor lined with polytetrafluoroethylene and reacted at 140 ° C for 6 hours. After the solution was cooled to room temperature, the collected precipitate was repeatedly washed three times with anhydrous ethanol and deionized water. After drying in a vacuum oven at 60 ° C for 6 hours, the Cl-doped octahedral Cu 2 O particle samples, prepared Cl-doped Cu 2 O octahedral particle samples were recorded as Cl-OCu 2 O-10.

[0025] Photochemical performance test: Cl-OCu 2 O-10 for photocatalytic reduction of CO 2 , methanol yield was 1440.80 μmol·g -1 , ethanol yield was 110.48 μmol·g -1 .

[0026] Example 4 Weigh 0.2g OCu 2 O was dispersed in 40 ml of deionized water, and then 0.015 g of NH 4Cl,. The solution was stirred for 20 minutes and then ultrasonically treated for 40 minutes. The solution was placed in a 50 ml stainless steel reactor lined with polytetrafluoroethylene and reacted at 140°C for 6 hours. After the solution was cooled to room temperature, the collected precipitate was repeatedly washed three times with anhydrous ethanol and deionized water. After drying in a vacuum oven at 60°C for 6 hours, the Cl-doped octahedral Cu 2 O particle samples, prepared Cl-doped Cu 2 O octahedral particle samples were recorded as Cl-OCu 2 O-15.

[0027] Photochemical performance test: Cl-OCu 2 O-15 for photocatalytic reduction of CO 2 , methanol production was 1469.51 μmol·g -1 , ethanol yield was 124.32 μmol·g -1 .

[0028] Example 5 Weigh 0.2g OCu 2 O was dispersed in 40 ml of deionized water, and then 0.025 g of NH 4 Cl,. The solution was stirred for 20 minutes and then ultrasonically treated for 40 minutes. The solution was placed in a 50 ml stainless steel reactor lined with polytetrafluoroethylene and reacted at 140°C for 6 hours. After the solution was cooled to room temperature, the collected precipitate was repeatedly washed three times with anhydrous ethanol and deionized water. After drying in a vacuum oven at 60°C for 6 hours, the Cl-doped octahedral Cu 2 O particle samples, prepared Cl-doped Cu 2 O octahedral particle samples were recorded as Cl-OCu 2 O-25.

[0029] Photochemical performance test: Cl-OCu 2 O-25 for photocatalytic reduction of CO 2 , methanol yield was 1451.26 μmol·g -1 , ethanol yield was 115.87 μmol·g -1 .

Claims

1. A method for preparing chlorine-doped Cu2O octahedral material, characterized in that: The following steps are involved: 1) Dissolve copper acetate in deionized water, then add NaOH and glucose, heat in a 60-80℃ water bath and stir continuously until the color of the solution no longer changes, cool to room temperature, centrifuge to obtain the precipitate, wash, and vacuum dry to obtain octahedral Cu2O particles, recorded as OCu2O; 2) OCu2O was stirred and dispersed in deionized water, and then NH4Cl was added and reacted at 120-140°C for 4-8 hours. After the reaction was completed, it was cooled to room temperature, centrifuged to obtain the precipitate, washed, and vacuum dried to obtain chlorine-doped octahedral Cu2O particles, which were recorded as Cl-OCu2O.

2. The method for preparing the chlorine-doped Cu2O octahedral material according to claim 1, characterized in that: The molar ratio of copper acetate to glucose is 4:1-6:1, and the molar ratio of NaOH to glucose is 25:1-35:

1.

3. The method for preparing the chlorine-doped Cu2O octahedral material according to claim 1, characterized in that: The mass ratio of OCu2O to NH4Cl is 8:1-20:

1.

4. Use of the chlorine-doped Cu2O octahedral material prepared by the method as claimed in claim 1 in the photocatalytic reduction of CO2 to produce alcohol.

5. The use of chlorine-doped Cu2O octahedral material in photocatalytic reduction of CO2 to produce alcohol as claimed in claim 4, characterized in that: After 5 h of catalytic reaction, the methanol yield reached 1440.80~2365.73 μmol·g -1 , ethanol yield was 110.48~150.06μmol·g -1 .